Role of dust loading in dynamic transport of semi-volatile organic compounds (SVOCs) into house dust: From multilayer to monolayer. (1st April 2023) - Cao, Jianping; Zhu, Yuqing; Huang, Xinyi; Zhang, Li; Wang, Xuanhao; Geng, Chuang; Huang, Haibao
Abstract: House dust is an important transfer and storage medium of semi-volatile organic compounds (SVOCs) in indoor environments. Dust loading (dust weight per surface area) has been identified as a key factor affecting SVOC transport into dust. As the increment of dust loading, house dust can be classified as monolayer and multilayer dusts. Most of existing studies have only investigated the multilayer dust though the monolayer dust is also ubiquitous on indoor surfaces, precluding the comprehensive explanation of dust loading effects. Therefore, this study proposed a mass transfer model to describe SVOC transport into house dust by differentiating SVOC diffusion distance in monolayer and multilayer dusts. High consistence between model predictions and measurements justified the model performance. Characteristic parameters of SVOCs in house dust, dust-air partition coefficient ( K d ) and diffusion coefficient ( D d ), were determined by fitting the model to the measurements. Further analysis indicated that: (1) SVOC transport mechanism in monolayer dust (dust size-dependent) was different from that in multilayer dust (dust loading-dependent), and (2) dust loading (in the range of 2.55–30 g/m 2 ) might have insignificant effects on K d . This study should be helpful for the deep understanding of SVOC transport into house dust and the accurate exposure assessment of indoor SVOCs. Highlights: Dust loading is as a key factor affecting the transport of SVOCs into house dust. Dust can be classified as monolayer and multilayer as the increment of dust loading. A model discriminating the thickness of monolayer and multilayer dusts was proposed. Consistence between predictions and measurements convinced the model performance. SVOC transport in monolayer dust is size-dependent instead of loading-dependent.